The Co‐Use of Tobacco and Cannabis Among Adolescents Over a 30‐Year Period2. (March 2014) - Webster, Lauren; Chaiton, Michael; Kirst, Maritt
ABSTRACT BACKGROUND This study explores the patterns of use and co‐use of tobacco and cannabis among Ontario adolescents over 3 decades and if characteristics of co‐users and single substance users have changed. METHODS Co‐use trends for 1981‐2011 were analyzed using the Centre for Addiction and Mental Health Ontario Student Drug Use and Health Survey, which includes 38, 331 students in grades 7, 9, and 11. A co‐user was defined as someone reporting daily tobacco and/or cannabis use in the past month. Trends over time (by gender and academic performance) were analyzed with logistic regression. RESULTS The prevalence of tobacco‐only use, cannabis‐only use, and co‐use fluctuated considerably. During 1981‐1993, there were more tobacco‐only users than co‐users and cannabis‐only users; since 1993 the prevalence of tobacco use has decreased dramatically. Co‐use prevalence peaked at 12% (95% confidence interval: 9, 15) in 1999, when prevalence of overall use of both substances was highest. In 2011, 92% of tobacco users also used cannabis, up from 16% in 1991. CONCLUSIONS In 2011 nearly all students who smoke tobacco daily also use cannabis. Non‐regular use of either substance is highest now compared with the past 3 decades. Contemporary tobacco and cannabis co‐users are significantly different than past users. Youth prevention programs should understand the changing context of cannabis and tobacco among youth.